Review of the Hidden Rays of Diffraction - 김세윤 (한국전자파학회, 2015)
A high-frequency analysis technique, called the hidden rays of diffraction (HRD), is reviewed in this paper. The physical optics and therigorous diffraction coefficients of a perfectly conducting wedge illuminated by a plane wave are compared. The physical existence ofhidden rays on the shadow boundary is explained in view of the geometric theory of diffraction (GTD). In particular, a systematic tracingof hidden rays and its visualization are precisely described by introducing the concept of the supplementary boundary. The physicalmeaning of the null-field condition in the complementary region is also explained.